2010
DOI: 10.1002/mds.23338
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal cardiac [123I]‐meta‐iodobenzylguanidine uptake in multiple system atrophy

Abstract: [(123)I]-Meta-iodobenzylguanidine (MIBG) myocardial scintigraphy is useful for distinguishing multiple system atrophy (MSA) from Parkinson disease. In this study, longitudinal observation using MIBG myocardial scintigraphy was carried out in patients with MSA to evaluate the association of myocardial MIBG uptake with clinical features. A total of 96 MIBG examinations were performed in 52 patients with MSA. The heart/mediastinum (H/M) ratio of MIBG uptake at 240 minutes after injection was below the lower limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
3
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(52 citation statements)
references
References 17 publications
(24 reference statements)
2
42
3
5
Order By: Relevance
“…It has been proposed that these cardiac imaging studies may help distinguish PD from MSA, where MIBG and 6-FDA scans are typically normal [73][74][75][76]. However, impaired MIBG uptake may also occur in some MSA cases with coexistent incidental Lewy body pathology [78]. This is consistent with findings that degeneration of cardiac sympathetic fibers may also occur in some MSA cases [21].…”
Section: Orthostatic Hypotensionmentioning
confidence: 77%
See 1 more Smart Citation
“…It has been proposed that these cardiac imaging studies may help distinguish PD from MSA, where MIBG and 6-FDA scans are typically normal [73][74][75][76]. However, impaired MIBG uptake may also occur in some MSA cases with coexistent incidental Lewy body pathology [78]. This is consistent with findings that degeneration of cardiac sympathetic fibers may also occur in some MSA cases [21].…”
Section: Orthostatic Hypotensionmentioning
confidence: 77%
“…However impaired MIBG uptake may also occur in a number of MSA cases [78] and may be of limited value in patients who have coexistent subclinical cardiac autonomic neuropathy, as occurs with diabetes mellitus.…”
Section: Clinical Markersmentioning
confidence: 97%
“…Recent myocardial innervation imaging with 123 I-MIBG scintigraphy also demonstrated a high sensitivity for PD detection and adequate specificity for discriminating between PD and MSA (Köllensperger et al, 2007;Chung et al, 2009;Fröhlich et al, 2010). However, Nagayama et al (2010) recently suggested that MSA cannot consistently be distinguished from PD based on 123 I-MIBG myocardial scintigraphy. Their study clearly showed that cardiac MIBG uptake is not always preserved in patients with MSA and that approximately 30% of patients with MSA showed decreased MIBG uptake without any correlation to disease duration or severity.…”
Section: Discussionmentioning
confidence: 99%
“…In multiple system atrophy (MSA) SPECT and 123 I-MIBG is usually considered as normal but recent studies have shown a [71][72][73]. This indicates that such tool cannot be reliably used for differential diagnosis in the clinical practice.…”
Section: Dysautonomiamentioning
confidence: 93%